Active nonsurgical decompression of large periapical lesions - 3 Case reports (2004)
This paper describes a new nonsurgical approach for treating large periapical lesions which involves using a modified vacuum system within the root canal space. This new technique produces a vacuum effect in the periapical zone, which facilitates evacuation of large amounts of inflammatory fluids. This technique was used in 3 clinical cases, in which the patients presented with copious amounts of exudate draining from within the root canals. Clinical and radiographic results showed long-term resolution of the endodontic lesions. This treatment of the periapical pathology was consistent with the principles of conservative, nonsurgical endodontic procedures.